EFEKTIVITAS IMPLEMENTASI CITES (CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA) DALAM MENGATASI PERDAGANGAN CULA BADAK DI VIETNAM - Dewi, Risma; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Rhinoceros or rhinocerotidae is a large mammal native to Africa and Asia. The entire rhinoceros family, the Rhinocerotidae, was included in Appendix I CITES (Convention on International Trade in Endangered Species of Wild Flora and Fauna) in 1997. It means trade of this species and their products is strictly prohibited for commercial purposes. However rhino population are in crisis, an instable demand for their horns is driving rhino poaching levels to unprecedented levels. Vietnam is directly responsible for high level of poaching in southern African countries. As the world’s largest consumer of rhino horn, the demand for rhino horn in Vietnam is driving the increase in rhino poaching crisis in South Africa and bring this species to extinction.This paper aims to describe the effectiveness of CITES implementation in tackling rhino horn trade in Vietnam, the reasons for the ineffectiveness of its implementations and determine the main factors that cause the ineffectiveness. To achieve this objectives, it is used a qualitative method through literature reviews and policy documents.The findings of this paper shows that the opportunity to increase the income offered by rhinoceros horn trading business can be a special attraction for the international mafia which ultimately makes it difficult for the government to apply the CITES regulations so that CITES implementation runs ineffectively and the rhino horn trade in Vietnam still continues.Keywords: rhinoceros, implementation, CITES, rhino horn trade,Vietnam